Perencanaan Arsitektur Enterprise Mengunakan Kerangka Kerja TOGAF ADM Pada Toko Ezra Computer - EZRA RESHYON SUSANTO (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
the Ezra Computer Store business process, there is still no information system, so that in the sales process errors often occur in making notes caused by human error. Among them, such as writing the wrong date of purchase and type of goods. Or even the note is lost and can't be found again. therefore we need an information system planning that can later be used by the owner to implement. The planning in this study uses the TOGAF ADM framework which consists of 8 phases that are useful in planning the enterprise architecture, but in this study only 4 phases will be used which are adjusted to the needs in the planning process at the Ezra Computer store. With this research, it is expected to be able to provide the results of an enterprise architecture plan that can be useful for Ezra Computer Stores in implementing information systems in their business processes. This enterprise architecture planning produces results in the form of a blueprint document that is useful for reference in developing technology in the Ezra Computer Store business process.